Chiral Diketopyrrolopyrrole-Helicene Polymer With Efficient Red Circularly Polarized Luminescence - Dhbaibi, Kais; Shen, Chengshuo; Jean, Marion; Vanthuyne, Nicolas; Roisnel, Thierry; Górecki, Marcin; Jamoussi, Bassem; Favereau, Ludovic; Crassous, Jeanne (Frontiers in Chemistry, 2020)
Chiral diketopyrrolopyrrole (DPP)-helicene polymers were synthesized to develop efficient red circularly polarized (CP) light emitters. These original chiral dyes display intense electronic circular dichroism (ECD) and CP luminescence (CPL) in the far-red spectral region owing to the presence of excitonic coupling between achiral DPP within the chiral environment of the polymeric structure. This work affords an interesting example illustrating the potential of pi-conjugated helical polymers for chiral optoelectronic applications.Circularly polarized (CP) light has received renewed attention owing to its superior potential over unpolarized one in a diverse range of domains such as (chir)optoelectronics (stereoscopic displays, organic light-emitting diodes (OLEDs), optical information processing, etc.) as well as in bio-imaging and chiral sensing